Impact of Work Demands on Burnout and Mental Health Among Frontline Nurses During COVID-19 - Ecker Albert; Anne Clare (Inovasi Analisis Data, 2024)
Objective: To investigate the impact of quantitative and emotional work demands on burnout and mental health outcomes among frontline nurses during the COV19 pandemic in Australia.Methods: A cross-sectional survey was conducted with a sample of frontline nurses in Australia to analyse the effects of work demands on burnout, emotional exhaustion and depersonalisation, and the mental health indices of anxiety, depression and stress. Data were collected through self-report surveys and linear and quantile regression analyses were used to assess the relationships between work demands and mental health outcomes.Findings: Increased quantitative and emotional work demands were found to significantly exacerbate burnout and mental health problems. This was particularly true for nurses with pre-existing mental health problems. The severity of these effects was more pronounced in those individuals who reported higher levels of anxiety, depression and stress.Novelty: This study contributes to understanding the heterogeneity of the impact of work demands on the mental health of frontline health workers during a global health crisis, focusing in particular on the differential impact according to the severity of pre-existing mental health conditions.Research Implications: The findings highlight the need for healthcare organizations to implement targeted mental health support and workload management strategies to mitigate burnout and support frontline staff well-being during and after crises such as the COVID-19 pandemic. Future research should investigate the long-term effects and effectiveness of workload reduction and mental health improvement interventions for nurses.